Student Variables and Senior Secondary Students’ Achievement in Mathematics in Rivers State, Nigeria - Ojimba, Daso Peter (Richtmann Publishing, 2012)
This research study focused on the relationship between the student variable and their achievement inmathematics at the senior secondary school level in Rivers State, Nigeria. The ex-post facto research designwas adopted for this study, since already conducted mathematics test scores of the students were retrievedand used for the analysis. Furthermore, data were elicited through the student variable and students’achievement in mathematics questionnaire (SVAMQ). This questionnaire consisted of five sections and wasadministered to the students. A population of 10,120 students were involved in the study out of which 4510were chosen for the sample using the Yarrow Yamen’s formula. The data were analyzed using the Z-teststatistic, means and simple percentage. The findings were that to a high extent students’ attitude towardsmathematics, their perceptions of the importance of mathematics and their self-concept influenced theirachievement in mathematics. Based on these findings, recommendations were made.